Accounting for slavery: masters and management - Rosenthal, Caitlin (Harvard University Press, 2018)
Accounting for Slavery offers a history of business and management practices on slave plantations in the British West Indies and the American South, covering the century from approximately 1780-1880. Far from lagging behind Northern manufacturers, the most sophisticated Southern planters used complex management techniques, measuring and monitoring their human capital with precision. More broadly, the book explores the complex relationship between slavery and capitalism in American history. The traditional story of modern management focuses on the factories of England and New England, largely ignoring plantation economies. Drawing on extensive archival research into plantation accounting practices, the author argues that the harsh realities of slavery were compatible with a highly quantitative, calculating style of management. Planters allocated and reallocated slaves' labor from task to task, precisely monitored their productivity, and depreciated their "human capital" decades before depreciation became a common accounting technique.–
OCLC: 1019844344
Keywords: Business History and race